2014
DOI: 10.1002/ptr.5264
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid Suppresses Lipid Accumulation by Suppressing Early Adipogenic Events and Cell Cycle Arrest

Abstract: Ellagic acid (EA) is a natural polyphenol found in various fruits and vegetables. In this study, we examined the inhibitory effect of EA on fat accumulation in 3T3-L1 cells during adipogenesis. Our data showed that EA reduced fat accumulation by down-regulating adipogenic markers such as peroxisome proliferator activated receptor γ (PPARγ) and the CCAAT/enhancer binding protein α (C/EBPα) at the mRNA and protein levels in a dose-dependent manner. We found that the decrease in adipogenic markers resulted from r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 28 publications
(35 reference statements)
3
15
0
Order By: Relevance
“…These results are in good agreement with a previous study by Woo et al. ( 2015 ), in which ellagic acid inhibits adipocyte differentiation by suppressing early adipogenic events and cell cycle arrest. Furthermore, Lee et al.…”
Section: Resultssupporting
confidence: 94%
“…These results are in good agreement with a previous study by Woo et al. ( 2015 ), in which ellagic acid inhibits adipocyte differentiation by suppressing early adipogenic events and cell cycle arrest. Furthermore, Lee et al.…”
Section: Resultssupporting
confidence: 94%
“…The protocol consisted of a 15-day exposure to the compound on a high-fat diet background, starting at the first feeding period. For example, curcumin [5053], indole-3-carbinol [54], baicalein [55], dieckol [56], ellagic acid [52], kaempferol [51], quercetin [56], seapolynol [57] and silibinin [58], have all been reported to inhibit lipid accumulation in these early, post-embryonic developmental stages, when the adipocyte lineage is just starting to be established [20,27]. In our work, we used the ZOT protocol at later larval developmental stages, when the animals had a well-established WAT [30].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the anti-inflammatory, anti-cancer and hepatoprotective effects of corilagin (35)(36)(37). Previous studies have also reported that ellagic acid improved hepatic steatosis and suppressed serum resistin levels in obese mice (38,39), and that ellagic acid suppresses lipid accumulation by inhibiting adipogenesis and cell proliferation (40). In a previous study, it was demonstrated that the anti-obesity effect of Geranium thunbergii was due to the presence of components including corilagin and ellagic acid (41).…”
Section: Discussionmentioning
confidence: 97%